2005
DOI: 10.1366/0003702052940495
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Infrared Spectra for Monitoring and Understanding the Kinetics and Mechanisms of Adsorption Processes

Abstract: Water adsorption onto thin zeolite 3A wafers has been investigated as a function of time, water vapor concentration, and zeolite sample mass using mid-infrared spectroscopy coupled with multivariate data analysis. Principal component analysis (PCA) of the spectral region of the water combination band was used for quantitative characterization of water adsorption onto the zeolite. The kinetics of the adsorption of water are found to be very reproducible and nearly linear with time. The kinetics of water adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Zhang et al 34 studied the water adsorption on thin zeolite 3A wafers by using mid-infrared spectroscopy coupled with multivariate data analysis. Their results demonstrated that zeolite 3A has three water adsorption sites or environments that are sequentially occupied.…”
Section: = [ + ]mentioning
confidence: 99%
“…Zhang et al 34 studied the water adsorption on thin zeolite 3A wafers by using mid-infrared spectroscopy coupled with multivariate data analysis. Their results demonstrated that zeolite 3A has three water adsorption sites or environments that are sequentially occupied.…”
Section: = [ + ]mentioning
confidence: 99%
“…The unique characteristic of functional group presented by the spectrum shows material properties, its behavior as well as specific components represented by their functional groups. This combination provides several advantages and is being followed for quality control in sevral area such as for determining nitrogen in soil by visible and near-infrared reflectance spectroscopy (Moron and Cozzolino, 2004), monitoring crystallization procedure and solid-state examination of crystalline product (Pollanen et al, 2005), and measuring the kinetics reaction of adsorption processes (Zhang et al, 2005).…”
Section: O N L I N E C O P ÿmentioning
confidence: 99%
“…Hence, by an appropriate selection of framework structure, cationic form, and (Si/Al) ratio, zeolites with quite different adsorptive properties must be existed. In most cases, zeolites with specific characteristics are desired; therefore, mixing the adsorptive properties to achieve a special selectivity is an option [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Structurementioning
confidence: 99%